iPSCs in NK Cell Manufacturing and NKEV Development - Boyd-Gibbins, Nicholas; Karagiannis, Peter; Hwang, Do Won; Kim, Shin-Il (Frontiers in Immunology, 2022)
Natural killer (NK) cell immunotherapies for cancer can complement existing T cell therapies while benefiting from advancements already made in the immunotherapy field. For NK cell manufacturing, induced pluripotent stem cells (iPSCs) offer advantages including eliminating donor variation and providing an ideal platform for genome engineering. At the same time, extracellular vesicles (EVs) have become a major research interest, and purified NK cell extracellular vesicles (NKEVs) have been shown to reproduce the key functions of their parent NK cells. NKEVs have the potential to be developed into a standalone therapeutic with reduced complexity and immunogenicity compared to cell therapies. This review explores the role iPSC technology can play in both NK cell manufacturing and NKEV development.